Evaluation and analysis of uncertainty in the information seeking behavior of medical post-graduate students - Azami Mohammad (Journal of Research in Medical and Dental Science, 2018)
This study aimed to explore and analyze uncertainty in the information seeking behavior among the students of Kerman University of Medical Sciences (KUMS) based on Kuhlthau Information Search Process Model. This is an applied research. Data gathered using questionnaire. Research population included 1075 students from all graduate students of KUMS in M.Sc. and Ph.D. grades. The sample size estimated 263 people .The studied students had relatively similar senses as reported by Kuhlthau in her information search process model. Among demographic variables, only gender affected the presentation stage. Women had better performance in the presentation stage. Ph.D. students performed better than master students when selecting their research topics. These two groups had no clear differences in other stages. Students with previous experience in research activities had better performance in title selection, literature exploration and presentation stages and also had lower uncertainty. The students’ performance decreased in different stages as their ages increased. The effect of individuals’ age on their performance was considerable in the stages of literature exploration and result presentation. The graduate students of KUMS follow the same stages as Kuhlthau information search process model and have similar feelings with that. Uncertainty was felt in the different stages of information search by graduate students of KUMS. The factors like age, gender, level of education and previous experience were effective in some stages on decrease or increase of uncertainty.